Controlled growth of TiO2/Zeolite nanocomposites for simultaneous removal of ammonium and phosphate ions to prevent eutrophication - Ashfaq, Muhammad Hamza; Shahid, Sammia; Javed, Mohsin; Iqbal, Shahid; Hakami, Othman; Aljazzar, Samar O.; Fatima, Urooj; Elkaeed, Eslam B.; Pashameah, Rami Adel; Alzahrani, Eman; Farouk, Abd-ElAziem; Somaily, H. H. (Frontiers in Materials, 2022)
In the modern era, problems like eutrophication caused by increased nutrients such as ammonia and phosphorous in freshwater bodies have become the cause of freshwater ecosystem deterioration. To save freshwater by reducing eutrophication, new cost-effective strategies and methods are urgently needed. In this study, titanium oxide nanoparticles dispersed on zeolite were chemically synthesized for the simultaneous removal of phosphate and ammonium ions from aqueous solutions. SEM and XRD analysis were used to characterize the synthesized TiO2/zeolite nanocomposites, which revealed that the synthesized material was more stable and dispersed than zeolite. The nanocomposites removed 38.8% NH4+ and 98.1% PO43- from an initial concentration of both ions of 20 mg 100 mL-1. The removal of both ions was investigated under various conditions including different concentrations of nanocomposites, initial concentration of the solution, temperature, time, and pH. The maximum adsorption of nanocomposites for PO43- was 38.63 mg g-1 at optimal conditions, and 3.75 mg g-1 for NH4+. Kinematics studies showed that both the ions were adsorbed by a pseudo-second-order model. Ion chemisorption occurred as a result of ligand exchange or electrostatic adsorption between ions and nanocomposites. Overall, it was determined that this strategy is a viable and efficient method for simultaneously removing both ions (anionic phosphate and cationic ammonium) from eutrophic waters.